Jesus’ Relationship with Women: A Biblical Approach to Violence against Women - Gómez Alarcón, Stalin (2021)
This article analyzes three gospel passages through the Expressive Arts method along with Biblical analysis. The passages are analyzed from three approaches: touch, body, and space. The expressive arts represent a therapy with art as a central element in an educational process. They create a safe environment to move towards a liminal space of imagination and reality, revealing everything that emerges from the arts. Furthermore, the expressive arts release the senses as well as the body significantly through creative movements, focusing on self-expression and bodynarrative. In this publication, Expressive Arts are applied to biblical passages in order to observe, describe and gather the biblical messages with the aim of conductin  theology to enlighten the particular reality of violence against women in Peru.